The Effect of Using the U-Dictionary Application for Students’ Pronunciation on Grade Eight in Teaching Speaking at SMP Swasta Taman Asuhan Pematang Siantar - Hutauruk, Rut Maria; Manihuruk, Leonita Maria Efipanias; Sitanggang, Anita (CV. Tripe Konsultan, 2024)
The objective of this research was to find out the effect of the U-Dictionary Application for the students’ pronunciation on grade eight in teaching speaking at SMP Swasta Taman Asuhan Pematang Siantar. The method used quantitative with quasi-experimental research method with pre-test and post-test design. Two classes provided the data: the experimental class and the control class. In this research, VIII-A was the experimental class, while VIII-B was the control class. There were 28 students in each class, for a total sample size of 56. The pre-test mean score for the experimental class was 64.75, whereas the mean score for the control class was 64.50. Conversely, the experimental class’s post-test mean score was 78.92, whereas the control class’s post-test mean score was 69.57. The data was then examined by the researchers using a t-test. The T-test showed a greater degree of significance (2,7 > 1.674) compared to the T-table. Results showed that using the U-Dictionary Application for students’ pronunciation on grade eight teaching speaking at SMP Swasta Taman Asuhan Pematang Siantar had a substantial impact. Ha was accepted and H0 was rejected.